FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TERJADINYA KARIES GIGI PADA SISWA KELAS V DI KECAMATAN TANJUNG REJO PERCUT SEI TUAN TAHUN 2017 - Damanik, Elsarika; Barus, Ernawati; Norleli, Norleli (UNIVERSITAS SARI MUTIARA INDONESIA, 2017)
Dental caries is the most common disease which always attacks human. Approximately 98% of the world population have dental caries problem. It is estimated that 90% of school children in the world have experienced dental caries in which the highest level of disease found in Asia and Latin America. According to a survey conducted by World Health Organization (WHO) in 2007, 20% children in Indonesia at the age of six years old have experienced with the dental caries. This percentage has increased to 60% at the age of 8 years old, 85% at the age of 10 years old and a remarkable rise to 90% in children at the age of 12 years old. The problems of dental caries in children becomes very important, especially at the primary school age children, since it is an indicator of success for children dental health care effort. In order to analyze factors associate with the occurrence of dental caries in children, a research has been conducted to the fifth-grade students of Kalam Kudus Primary School using quantitative method with the total of 128 respondents. The research found that there is a significant correlation between the level of knowledge attitudes, education, income,and diet provided by their parents and the occurrence of dental caries. Moreover, the income of parents also contributes to thedental caries problem. It is expected that parents to give more attention and keep the healthy diet of their children in order to avoid the dental caries. In addition, the Health Agency at Siantar City needs to conduct socialization more regularly on oral health particularly to school children on the dental caries